CD20‐positive plasmablastic lymphoma with excellent response to bortezomib combined with rituximab. (1st April 2014) - Yan, Min; Dong, Zhaoming; Zhao, Frank; Chauncey, Thomas; Deauna‐Limayo, Delva; Wang‐Rodriguez, Jessica; Liu, Dayu; Wang, Huan‐You; Pilz, Renate
Abstract As a distinct type of aggressive mature large B‐cell lymphoma, plasmablastic lymphoma (PBL) poses diagnostic and treatment challenges. PBL is distinguished from other B‐cell lymphomas by the presence of plasmacytic differentiation markers such as CD38, CD138, and MUM1. Clinically, PBLs from oral and extra‐oral sites are rapidly progressive tumors with frequent relapse after treatment with standard diffuse large B‐cell lymphoma regimens. Here, we report a near‐complete response of one patient with relapsed PBL following treatment with a non‐cytotoxic regimen containing bortezomib, rituximab, and dexamethasone.